Utilization of the Greater Mekong Subregion Cross-Border Transport Agreement (GMS-CBTA) - Suvakunta, Pittaya; Prasertsak, Viralbajra; Chaiphiphat, Theraphat; Lertpusit, Sivarin; Naruepatarawanon, Weera (WIMAYA, 2024)
The aim of this study was to analyze spatial data on the current status and progress in the implementation of the Greater Mekong Subregion (GMS) Cross-Border Transport Agreement (CBTA). Problems, obstacles, and opportunities related to the agreement during implementation were examined. This qualitative research was performed using field surveys, stakeholder interviews, and brainstorming in focus groups. The results revealed that there is a need to develop road and rail transportation systems that connect with the customs houses of Mae Sai, Chiang Saen, Chiang Khong, Nakhon Phanom, and Nong Khai in Thailand. Cross-border transportation with neighboring countries needs to be improved as well because the transportation through customs houses is cheap and provides certain schedules. Cross-border regulations were found to be a major obstacle. In order to promote smooth cross-border transportation, negotiations at the state-to-state level and private-to-private level are needed. The connection of logistics networks under the GMS-CBTA framework will be flexible and can be adjusted according to the changing situations in the region and globally. Cooperation of the GMS in the transportation system could provide a mainland link that connects the Indian Ocean with the Pacific Ocean. It could provide a short and fast alternative route that could promote the potential of GMS competition at a global level, enhance bargaining power, and maintain the balance of power in the region.